Analisis Pelayanan Terminal 3 Bandar Udara Internasional Soekarno Hatta Ditinjau dari Sisi Fasilitas Bandar Udara, Maskapai dan Penumpang - Pramesti, Rizki Rahmalta; Kurniawan, Jermanto Setia; Irenita, Novembriani (Jurnal Sistem Transportasi & Logistik, 2025)
Terminal 3 is one of the terminals located at Soekarno Hatta Airport. This terminal has international and domestic airline services for as many as 37 airlines. Problems in service still often occur, both problems in terms of facilities, airlines or passengers such as queued check-in counters, requests for golf car services, far gate complaints, lost & found, no gate listed, delayed and others. In this study, to find solutions to problems in aviation services, a research approach was carried out using quantitative methods between airport facilities, airlines and passengers by distributing questionnaires to passengers and analyzed to determine the relationship between services at Terminal 3 from these three sides. Based on the results of the regression analysis using SPSS 24 software, it was found that airport facilities were 0.642, airlines were 0.295 and passengers were 0.040 so that they had a positive or simultaneous effect on service, and with partial hypothesis testing, facilities and airlines had an effect on service, while passengers had no effect.